Characteristics, complexation and analytical methods of darunavir - Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
What is it? Darunavir is a protease inhibitor used in the treatment of HIV infection. It is an important drug of therapy cocktail for patients infected with the virus. On the market there are darunavir ethanolate tablets of 75, 150, 300, 400, 600 and 800mg, because this is the most stable form. It is commercialized by Janssen-Cilag with the name PrezistaTM. Why we started? This drug has low water solubility and poor bioavailability, therefore requires administration in doses relatively high to the success of the therapeutic effect. The complexation of drugs by using cyclodextrin is welcome in this respect to improve the solubility and hence increase the dissolution rate of poorly soluble drugs. A monograph about this compound has not been described, thus it is an extremely important quality control of darunavir to demonstrate its effectiveness and safety. What we did? Some existing analytical techniques have been discussed in this manuscript, focusing on bioanalytical and pharmaceutical quality control applications. What we found? This review showed the published analytical methods reported for the determination of darunavir and discuss about its characteristics and complexation with cyclodextrin.
Keywords: Antiretroviral; Analytical methods; Complexation; Cyclodextrin; Darunavir; Quality control